The hero with a thousand faces - Campbell, Joseph, 1904- (Princeton, N.J. : Princeton University Press, 1972)
Examines myths and folk tales from around the world in an attempt to understand the symbolism of the hero as it appears in the mythologies and religions of mankind.
Includes bibliographical references and index.
University Press Titles (A.A.S.L./P.L.A.).
Young Adult
Keywords: Mythology; Psychoanalysis; Mythology; Psychoanalysis